KAJIAN BERBAGAI TIPE PENGELOLAAN WILAYAH SUNGAI DI ASIA SEBAGAI ACUAN DALAM PENENTUAN SISTEM PENGELOLAAN SUMBER DAYA AIR - SURYA DEWI, NI MADE NIA BUNGA (Universitas Mahasaraswati Mataram, 2019)
The Integrated Water Resources Management (IWRM) is significant to do in order to obtain water supply availability including inter-sector perspective, diverse of water future needs, and its present availability and orientation towards the 'triple bottom line', such as social, economi,c and environment. In the past decade, most countries in Asia have already adopted national water policies that advocate IWRM in river basins. However, IWRM implementation is still at an early stage. IWRM at the basin level is best provided by a River Basin Organization (RBO) by facilitating and/ or implementing various development processes and management. Across Asia, a variety of small and large RBOs are now helping governments and stakeholders to implement IWRM in river basins. Some RBOs operate within the structures of regular government departments. In other cases, however, a corporate or quasi-corporate model has been selected, to provide RBOs with greater autonomy in their management, capacity development, and revenue generation. The research attempts to study distinction between three types of RBO: council/committee, public/ government, and corporation. Thus, it can determine the most appropriate type of river management applied in river basin